Machine Learning Approach Regarding The Classification And Prediction Of Dog Sounds: A Case Study Of South Indian Breeds - Prabu Mohandas; Jerline Sheebha Anni; Khairunnisa Hasikin; Dhayalan Velauthapillai; Veena Raj; Thanihaichelvan Murugathas; Rajkumar Thanasekaran; Muhammad Mokhzaini Azizan (MDPI, 2024)
Indexed by WOS/SCOPUS